(untitled) (Nepalese Journal of Radiology, 2022)
Introduction: The main aim of this study was to determine the mean value of liver stiffness in healthy adults using S-Shear wave elastography and compare liver stiffness with gender, age and BMI. Methods: A hospital-based cross-sectional study was carried out in the Department of Radiology, BPKIHS over 6 months after taking ethical approval from the institutional review committee. Ninety-six adults referred for ultrasonography of the abdomen for various indications were included in the study Results: Mean shear wave velocity of the healthy liver in the study subjects was 1.267±0.151m/s.The corresponding mean value of liver stiffness was 4.91±1.15 kPa. The mean liver stiffness was higher in males compared to females (5.283±1.08 kPa vs. 4.689±1.13 kPa) which were statistically significant (p=0.0013). Mean liver stiffness was highest in the age group of 70-79 years (6.7±0.80 kPa) compared to other age groups. There were significant differences between the mean liver stiffness values among different age groups (p=0.01). Patients in the obese class I category showed higher mean liver stiffness value (5.54±0.42 kPa) than other BMI categories. However, mean liver stiffness values showed no significant difference among different BMI groups (p=0.322). Conclusions: Liver stiffness values measured using S-Shear wave elastography in healthy adults ranged between 2.4 kPA to 7.4 kPa.There were significant differences in mean liver stiffness values between men and women and among different age groups. However, no significant difference was found among different BMI categories.